THE EFFECT OF PROBLEM-BASED LEARNING (PBL) ON THE CRITICAL THINKING OF STUDENTS IN ECONOMICS CLASS XI AT MA AS SALAMAH IN THE 2024-2025 ACADEMIC YEAR - Ulfatun Hasanah; Miftahus Surur; Sri Ayudha Mujiyanti (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
Education plays a very important role in improving the quality of human resources. One of the main problems in education in Indonesia is the low learning outcomes of students, partly due to the use of inappropriate learning methods. The problem-based learning (PBL) model is one approach that can improve students' critical thinking skills because it emphasizes active and independent solving of real problems. This study aims to determine the effect of the problem-based learning (PBL) model on students' critical thinking skills in Economics class XI at MA As Salamah in the 2024/2025 academic year. The background of this study is the low critical thinking skills of students due to conventional learning methods. The approach used was quantitative with simple linear regression analysis. The research instruments were tested for validity and reliability, with all items declared valid (r > 0.306) and reliable (α = 0.802 for X and 0.797 for Y). The normality test showed that the residual data were normally distributed (p = 0.200; Monte Carlo Sig. = 0.841). The regression analysis results showed an R value of 0.965 and an R² value of 0.932, and the t-test showed a significant effect of variable X on Y (p < 0.001). Thus, PBL has a positive and significant effect on students' critical thinking skills.